Conducting nano-channels in an induced piezoelectric polymeric matrix using swift heavy ions and subsequent functionalization - Jana K.K.; Ray B.; Avasthi D.K.; Maiti P. (My University, 2025)
Nanohybrids of poly(vinylidene fluoride) with layered silicates have been synthesized by melt extrusion and nano-channels have been fabricated by swift heavy ion (SHI) irradiation followed by chemical etching of the selective amorphous zones in the latent tracks. The channel diameter was reduced to 30 nm in the presence of nanoclay in the nanohybrid, making it suitable for membrane applications. Grafting with styrene was carried out inside the nano-channels using the free radicals created by the SHI exposure. Sulphonation on the grafted polystyrene was carried out to increase the conductivity of the membrane to the semiconducting range through ion channel conduction. The grafting and sulphonation inside the nano-channels were confirmed through spectroscopic techniques viz. NMR, FTIR, UV and molecular weight measurements. The dimensions of the channels are controlled by the SHI fluence and thereby dictates the properties including 10 orders of magnitude higher conductivity by creating a greater number of channels and hence increasing the surface area required for enhanced grafting and sulphonation. The hetero-junction and nano-channel conduction was demonstrated through STM measurements showing that the superior conduction depends on the relative extent of grafting and sulphonation in pure PVDF and the nanohybrid. The matrix PVDF crystallizes in the piezoelectric β-phase in the presence of nanoclay and promotes the formation of smart membranes. © 2012 The Royal Society of Chemistry.